PENGARUH DIVIDEND YIELD, RETENTION RATIO, EPS, DAN ROE TERHADAP HARGA SAHAM - Rista Puput Aryanti (ITB AAS INDONESIA Surakarta, 2021)
This research intends to analyze the influence of Dividend Yield, Retention Ratio, Earnings per Share (or EPS), and Return on Equity (or ROE) on the Stock Price. It examines arrange of data set form Banks Company and in Indonesia Stock Exchange between 2012-2014. The researcher utilizes purposive sampling method with 25 Banks Company. The analysis technique used here is multiple regression with the least square difference and hypothesis test using t-statistic to examine partial regression coefficient and f-statistic to examine the mean of mutual effect with level of significant 5%. Keywords: Dividend Yield, Retention Ratio, EPS, ROE, and Stock Price